Zone for collecting the ions of a given mass range in the plasma filter of masses - Katrechko, V.V.; Yuferov, V.B.; Ilichova, V.O.; Svichkar, A.S.; Khizhnyak, S.N. (Вопросы атомной науки и техники, 2020)
The trajectories of motion for atomic and molecular ions of a given mass range (M = 232...277) in the plasma mass filter, which is currently being developed, are calculated. The influence of the initial conditions (energy, angle, radius) on the ion trajectory to determine the dimensions of the collector for actinides, the so-called “pocket”, is studied. It is shown that the variable component of the radial electric field, tuned to a frequency equal to half the ion cyclotron frequency for M = 238 allows target ions to enter the “pocket”. An analysis of the calculations showed that there are limitations on energy, angle, and radius related to the initial conditions for the ion motion, that must be taken into account when creating the plasma source for the plasma mass filter.